Regional Climate Modeling over South America: A Review - Solman, Silvina Alicia (2013)
This review summarizes the progress achieved on regional climate modeling activities over South America since the early efforts at the beginning of the 2000s until now. During the last 10 years, simulations with regional climate models (RCMs) have been performed for several purposes over the region. Early effortsweremainly focused on sensitivity studies to both physicalmechanisms and technical aspects of RCMs. The last developments were focused mainly on providing   high-resolution information on regional climate change. This paper describes the most outstanding contributions fromthe isolated efforts to  the ongoing coordinated RCM activities in the framework of the CORDEX initiative, which represents a major endeavor to produce ensemble climate change projections at regional scales and allows exploring the associated range of uncertainties. The remaining challenges in modeling South American climate features are also discussed.